Bimodal Fluorescence and Magnetic Resonance Imaging Using Water-Soluble Hexagonal NaYF4:Ce, Tb, Gd Nanocrystals. (14th December 2011) - Ren, Wen Ting; Liang, Liang Bo; Qi, Fei; Sun, Zheng Bo; Yang, Zhi Yong; Huang, Xiao Qi; Wu, Qi Zhu; Zhu, Hong Yan; Yu, Xue Feng; Quan, Hong; Gong, Qi Yong
Abstract : The present study explored the feasibility of using hexagonal-phase NaYF4 :Ce, Tb, Gd nanocrystals as bimodal probes for fluorescence and magnetic resonance (MR) imaging. Using a facile and user-friendly strategy, the NaYF4 :Ce, Tb, Gd nanocrystals were synthesized with good water dispensability, high quantum yield (26%), and decent MRT 1 relaxivity (r 1 = 2.87 mM −1 s −1 ). The NaYF4 :Ce, Tb, Gd NCs conjugated by folic acid presented great efficiency in fluorescence imaging of C6 glioma cells in vitro . Meanwhile, in in vivo MR experiments on rats, the NaYF4 :Ce, Tb, Gd NCs also significantly increasedT 1 signal in the liver, spleen, and kidney even with a low probe dose. The proposed NaYF4 :Ce, Tb, Gd nanoprobes hold promise for simultaneous bimodal fluorescence and MR bioimaging.